2011
DOI: 10.1371/journal.pone.0022232
|View full text |Cite
|
Sign up to set email alerts
|

A Tri-Oceanic Perspective: DNA Barcoding Reveals Geographic Structure and Cryptic Diversity in Canadian Polychaetes

Abstract: BackgroundAlthough polychaetes are one of the dominant taxa in marine communities, their distributions and taxonomic diversity are poorly understood. Recent studies have shown that many species thought to have broad distributions are actually a complex of allied species. In Canada, 12% of polychaete species are thought to occur in Atlantic, Arctic, and Pacific Oceans, but the extent of gene flow among their populations has not been tested.Methodology/Principal FindingsSequence variation in a segment of the mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
228
3
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(250 citation statements)
references
References 73 publications
(110 reference statements)
16
228
3
3
Order By: Relevance
“…Fauvel (1927), comprise a wide variety of characters and probably comprise more than one species under this name . Likewise, molecular analyses by Carr et al (2011) revealed at least two putative cryptic species in Canadian waters (one in the Arctic, another in the Pacific Ocean) which were initially identified as Bradabyssa villosa. restricts Bradabyssa villosa sensu stricto to the North Atlantic Ocean and European and Russian Arctic and re-instates Bradabyssa parthenopeia (Lo Bianco, 1893) from the Mediterranean (Gulf of Naples) -a species previously considered a synonym of Bradabyssa villosa.…”
Section: Novafabricia Posidoniae Licciano and Giangrande 2006mentioning
confidence: 99%
See 2 more Smart Citations
“…Fauvel (1927), comprise a wide variety of characters and probably comprise more than one species under this name . Likewise, molecular analyses by Carr et al (2011) revealed at least two putative cryptic species in Canadian waters (one in the Arctic, another in the Pacific Ocean) which were initially identified as Bradabyssa villosa. restricts Bradabyssa villosa sensu stricto to the North Atlantic Ocean and European and Russian Arctic and re-instates Bradabyssa parthenopeia (Lo Bianco, 1893) from the Mediterranean (Gulf of Naples) -a species previously considered a synonym of Bradabyssa villosa.…”
Section: Novafabricia Posidoniae Licciano and Giangrande 2006mentioning
confidence: 99%
“…Consists of at least two different putative cryptic species in the Arctic Ocean (Carr et al 2011), specimens from other locations could belong to either of these or to a different cryptic species. considers the distribution of Flabelligera affinis to be restricted to "Arctic to cold and temperate, boreal localities" and questions the identity of specimens reported under this name from warm water localities such as Africa or Panama.…”
Section: Flabelligera Affinis M Sars 1829mentioning
confidence: 99%
See 1 more Smart Citation
“…With the rapid development of molecular tools, they have been recognized as necessary for delineating species boundaries, quantifying diversity, and clarifying distributions in understudied groups (Westheide & Schmidt, 2003;Carr et al, 2011). Mitochondrial DNA (mtDNA) has been applied widely in the studies of phylogenetics and evolution as well as an effective marker to assist taxonomy because of its uniparental inheritance (in a majority of animal phyla), high evolutionary rate, lack of introns, large copy numbers in every cell, and limited recombination (Adriana et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Several cases of cryptic species have been reported for marine species with relatively wide geographical range and low dispersal potential (BAIRD et al, 2011;BOISSIN et al, 2008;CARR et al, 2011;HELD;WÄGELE, 2005;LARSEN et al, 2014;MARKOW;PFEILER, 2010;RAUPACH et al, 2007;REMERIE et al, 2006;SPONER;LESSIOS, 2009;VARELA;HAYE, 2012;XAVIER et al, 2016). In a low dispersal scenario, as in many marine brooders, isolation by distance and outbreeding depression are enough to account for a high speciation rate (HOELZER et al, 2008).…”
mentioning
confidence: 99%